Edukasi Hipertensi Berbasis Bahasa Banjar dan Pemanfaatan Infused Water Mentimun pada Lansia di Panti Uma Kandung - Rian Tasalim; Naili Rahmah; Nur Fitriana; Resty Aulia Ramadini; Tasya Tria Ananda Ananda; Ridha Risalda Lauzia; Siti Rahmah; Muhammad Arief Wicaksono; Rifa’atul Mahmudah; Muhammad Riduansyah (Institut Kesehatan Suaka Insan, 2026)
Hypertension is a prevalent health issue among the elderly, contributing to severe cardiovascular complications. Indonesia’s 2018 Basic Health Research (Riskesdas) reported that hypertension affects more than 50% of older adults aged 65–74 years. This community service program aimed to improve elderly knowledge and skills in hypertension prevention through Banjar language-based education and the use of cucumber infused water as a complementary approach. A participatory method was applied, involving lecturers, students, and 30 elderly residents at Uma Kandung Social Nursing Home, Banjarmasin. Activities included blood pressure measurement, health education in Banjar language, cucumber infused water preparation, blood pressure monitoring practice, and evaluation with pre- and post-tests. Findings indicated improved knowledge from 40% to 83% and a reduction in systolic blood pressure by 8–10 mmHg and diastolic by 5–7 mmHg. Participants also showed higher motivation for routine monitoring and healthier lifestyles. In conclusion, integrating culturally based education with cucumber infused water is effective in enhancing health literacy and promoting hypertension control behaviors among the elderly.